A High-Voltage Integrated Circuit Engine for a Dielectrophoresis-based Programmable Micro-Fluidic Processor - Current, K. Wayne (2005)
A high-voltage (HV) integrated circuit has been demonstrated to transport droplets on programmable paths across its coated surface. This chip is the engine for a dielectrophoresis (DEP)-based micro-fluidic lab-on-a-chip system. This chip creates DEP forces that move and help inject droplets. Electrode excitation voltage and frequency are variable. With the electrodes driven with a 100V peak-to-peak periodic waveform, the maximum high-voltage electrode waveform frequency is about 200Hz. Data communication rate is variable up to 250kHz. This demonstration chip has a 32×32 array of nominally 100V electrode drivers. It is fabricated in a 130V SOI CMOS fabrication technology, dissipates a maximum of 1.87W, and is about 10.4 mm × 8.2 mm.